Synergistic effect of early enteral and parenteral nutrition on immune and nutritional recovery following gastric cancer surgery - Tao, Jialong; Du, Xiuluan; Xu, Haixia; Dai, Liya; Zhang, Chen; Gao, Wenwen; Huang, Sijia; Wang, Yanjie; Sun, Jing; Zhao, Wenlu (Frontiers in Surgery, 2026)
ObjectiveIn this study, we aimed to explore the effects of early enteral nutrition (EN) combined with parenteral nutrition (PN) on the immune function and nutritional indices in patients with gastric cancer (GC) after surgery.MethodsA total of 100 patients who underwent radical gastrectomy in our hospital between June 2022 and June 2023 were selected and divided into control (CG) and observation (OG) groups. The patients in the CG received early EN support, whereas those in the OG received early EN combined with supportive PN treatment. Gastrointestinal functional recovery, length of hospital stay, nutritional indices, immune function, inflammatory stress index, and the incidence of complications in both groups were compared.ResultsThe time to first flatus, time to first defecation, time to tolerance of semi-liquid diet, and the length of hospital stay were shorter in the OG than that in the CG (P < 0.05). After nutritional support, the albumin, total protein (TP), and transferrin levels in the OG were higher than those in the CG (P < 0.05). In addition, immunoglobulin (Ig)G, IgM, and IgA levels were higher in the OG group than those in the CG group (P < 0.05). Moreover, tumor necrosis factor-α, IL-6, and C-reactive protein levels in the OG were lower compared to those in the CG (P < 0.05). The incidence of complications was lower in the OG than in the CG (P < 0.05).ConclusionFor patients with GC, the combined application of early EN and PN support measures after surgery can accelerate the recovery of gastrointestinal function, reduce complications, improve the body's nutritional status, promote the recovery of immune function, and lower the inflammatory stress response.